Family history as a risk factor for menstrual dysfunction in adolescent girls - Багацька, Н. В.; Дємєнкова, І. Г.; Начьотова, Т. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The results of genealogical analysis carried out in families of adolescent girls with such disorders of menstrual function onset as puberty uterine bleeding (PUB), oligomenorrhea (OM) and secondary amenorrhea (SA) have been presented. The menstrual dysfunctions have started their manifestation in the first year of the menarche in 49 patients with oligomenorrhea, in 47 patients with puberty uterine bleeding and in 42 patients with secondary amenorrhea. The genealogies analysis has shown that the hereditary load by gynecological diseases occurs in 70.2% of girls with PUB, 69.4% of girls with OM and in 78.6% girls with SA. Among the relatives of probands in all surveyed groups gynecological diseases (except inflammation) were more often diagnosed in mothers of girls: in 53.2% of mothers of girls with PUB, in 53.1% of mothers of girls with OM and in 52.4% of mothers of girls with SA. Quite often gynecological pathology was diagnosed in grandmothers and aunts of probands. When analyzing the overall frequency of gynecological diseases among relatives of girls with menstrual function disorders we have established an increased frequency of the studied disease in I degree relatives compared with relatives of II and III degrees of relationship in all groups of observation. The analysis of genealogies of patients’ families allowed establishing the presence of diseases of endocrine, cardiovascular, gastrointestinal systems and cancer in relatives of three degrees of relationship.